PENERAPAN MODEL PEMBELAJARAN KEPALA BERNOMOR STRUKTUR UNTUK MENINGKATKAN AKTIFITAS BELAJAR DAN HASIL BELAJAR 104 SISWA KELAS IX-A SMP NEGERI 5 PANJI SITUBONDO (IKIP PGRI Jember, 2017)
The purpose of this study is to improve student learning activities in the implementation of the headed structural number learning model, of subjects IPS basic competence describe international trade and its impact on the economy of Indonesia class VIIIA Odd Semester in SMP Negeri 5 Panji Situbondo. Stages of research there are 4 namely: planning, action, observation and reflection. This is done in two cycles. Informations collected through observations, interviews, written subjective. The learning outcomes in cycle II has increased in cycle 2 there is an increase in learning outcomes from cycle 1 by 71% increased 22% so that in cycle 2 to 94%. Before implemented the model of learning head numbered learning outcomes on the cycle showed 71% with 24 students who completed while 10 students or 29% not been said complete because under the average class. However, after the learning model numbered head on the cycle 2 learning outcomes increased to 94% or 32 students whocompleted the classical and 2 unfinished students or 6%.